IMPLEMENTATION OF VOICE RECOGNITION TECHNOLOGY ON ENGLISH LEARNING APPLICATION BY SELF LEARNING BASED ON ANDROID DEVICE - Derwin Suhartono; Calvin Calvin; Mery Yustina; Shandy Kurniawati; Haryono Soeparno; Fredy Purnomo (Prosiding SNST Fakultas Teknik, 2013)
Nowadays, English is going global; it has forced almost all parts of the world to use English as the main  communication language. The growth of media  needs  to learn English  is also run rapidly. This prompted the need of many tools or media  that can be used as a  tool  to  learn English  well. In this research,  the  application  development  as a  learning  device  for  self-learning using Android  is done by embedding voice recognition technology  in it. The method used here is embedded speech recognition method. Embedded speech recognition method is often used in mobile application and it is simpler than  either network speech recognition or distributed speech recognition. This is due to the lack of signal transmission from the client to the remote  server. The application is developed to support English learning especially for listening and speaking. Keywords: Android, English, Self Learning, Voice Recognition